Didactic strategy to contribute to the development of communicative competence in Health Psychology students - Ana María Molina Gómez; Angelina Roméu Escobar; Miriam Gutiérrez Escobar; María Elinor Dulzaides Iglesias (Medisur, 2011)
Background: the cognitive, socio-cultural and communicative language teaching approach reveals the importance of syntactic speech closely related to semantic and pragmatic dimensions and aimed at understanding, analysis and construction of discourse. Objective: to design a didactic strategy that contributes to the development of communicative competence. Methods: pedagogic research on the teaching- learning process of Spanish grammar for first year students of Health Psychology in the University of Medical Sciences of Cienfuegos. The amount of knowledge students have on grammatical contents and functionality of the structures in the text and their perception and the one from former teachers on the importance of grammatical knowledge and the way it is addressed were determined. Methods used: analytic and synthetic; logical and historical; inductive and deductive; systemic, structural and modeling; as well as a desk study, surveys, diagnostic testing and consulting experts. Results: the methodologies for teaching grammar in previous educational levels do not enhance the development of communicative competence. Changes were made on the syllabus according to the cognitive, communicative and sociocultural approach and a teaching strategy successfully assessed by experts and involving the treatment of grammar from a communicative-functional perspective using this approach was proposed. Conclusions: a teaching strategy based on the cognitive, communicative and sociocultural approach for teaching Spanish grammar contributes to the development of communicative competence.